Virtual learning experimentation with student facilitator and explaining (SFAE) on mathematical representation abilities and understanding mathematics concepts - Indah Resti Ayuni Suri; Netriwati Netriwati; Fanny Kusumaningtyas; Suherman Suherman (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
In the rapidly evolving world of education, particularly within STEM disciplines, innovation in teaching methods is crucial. This study explores the potential of a new learning approach designed to address the deficiencies of traditional methods, with a focus on mathematics at the secondary school level. The researchers aimed to test the effectiveness of a Virtual Learning model using the Student Facilitator and Explaining (SFAE) approach in enhancing mathematical representational skills and conceptual understanding among high school students. A total of 120 students participated in the study, divided into two groups: 60 students in the experimental group received SFAE-based learning, and 60 students in the control group were taught using standard expository methods. Utilizing a control group design and post-test, the research revealed significant improvements in the experimental group's mathematical representation abilities and conceptual understanding compared to the control group. These findings demonstrate that integrating the SFAE approach within virtual learning environments not only broadens the scope but also enhances the quality of mathematical understanding. This study underscores the substantial potential of innovative learning approaches in the digital era, providing effective solutions to challenges in mathematics education.